2000
DOI: 10.3928/0147-7447-20001001-17
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting Local Bone With Grafton Demineralized Bone Matrix for Posterolateral Lumbar Spine Fusion: Avoiding Second Site Autologous Bone Harvest

Abstract: Mineralization and integrity of the bone graft mass were evaluated among patients having posterolateral fusion. Grafting consisted of a composite of Grafton and "local" autologous bone (n=56) or iliac crest autograft alone (n=52). Mineralization was rated radiographically at baseline and at 3, 6, 12, and 24 months. Integrity was judged as fused or not fused. Mineralization ratings did not differ significantly between groups at any postoperative interval (P values of .25-1 .00). The percentage of patients fused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…Six studies on DBM, 1 noninstrumented 53 and 5 instrumented, 9,54 -57 were included in this review. Five (4 prospective and 1 retrospective) studies looked at DBM in posterior fusion, 9,53 -56 and one prospective study utilized DBM for both anterior and posterior procedures. 57…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies on DBM, 1 noninstrumented 53 and 5 instrumented, 9,54 -57 were included in this review. Five (4 prospective and 1 retrospective) studies looked at DBM in posterior fusion, 9,53 -56 and one prospective study utilized DBM for both anterior and posterior procedures. 57…”
Section: Resultsmentioning
confidence: 99%
“…Three studies, 2 prospective and 1 retrospective, utilized a combination of DBM and autograft in PLF/PLIF, TLIF, or ALIF procedures. 55 -57 In a prospective case-control study, 56 patients underwent PLF or PLF/PLIF with Grafton DBM and local autograft, and 52 patients received ICBG. 55 At 24 months, the results showed a 60% fusion rate in the DBM and a 56% fusion rate in the control group (Tables 2 and 3).…”
Section: Resultsmentioning
confidence: 99%
“…There is a study somewhat encouraging, which compared the fusion rates of auto-local bone and DBM constructs to that of the auto-iliac bone alone cases in the setting of PLF. The result that presented no difference between the two groups indicated that it has a value as a graft extender in humans [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we concluded that it does not indicate inconsistent osteoinductivity, but unwarrantable osteoinductivity. Sassard et al [ 21 ] reported that DBM acted as a graft extender when it was mixed with auto-iliac bone in 3:1 ratio. In my opinion, that cannot be as an osteoinductive material.…”
Section: Discussionmentioning
confidence: 99%
“…Radiographic progression of the fusion with time was also shown when DBM was used as bone graft extender to decrease the need of autologous bone graft [ 14 ]. Intra-individual comparison of DBM augmented autograft at one side and autograft without adjunct at the contralateral side in patients who underwent postero-lateral fusion showed equal results in radiographic assessment [ 15 ]. An ex vivo histological analysis of different types of DBM products used for sinus lift procedures in oral surgery showed superiority of DBX® in terms of new bone formation and low residual demineralised matrix compared to other products [ 16 ].…”
Section: Discussionmentioning
confidence: 99%